Active and integrated electronic metadevices for future telecommunication circuits - Mohammad Samizadeh Nikoo; Chenhao Chu; Boce Lin; Yuqi Liu; Youngin Kim; Hua Wang (Communications Engineering)
Abstract The rise of data-driven demands calls for terahertz-capable circuits, however, semiconductor devices still face performance limitations above 100 GHz, posing a challenge for wireless networks. Electronic metadevice is a concept inspired by optical metamaterials, which was first demonstrated in the form of switches that could challenge the limitations of traditional semiconductor devices. Here we unveil critical aspects of this technology and demonstrate three-terminal active metadevices, which show promise for the next generation of telecommunication circuits. We show near-ideal linear and nonlinear operation of electronic metadevices, approaching the material limits, and by monolithic integration of electronic metadevices, we demonstrate picosecond terahertz switches with low insertion loss and high isolation. We finally present three-terminal metadevices offering parametric amplification and active mixing, which show ultrawideband operation, supporting data-rates exceeding 40 Gbps. Our work provides a solution for future ultrafast electronics with applications in 6 G telecommunications, enabling the development of new functional devices based on the electronic metadevice concept.